The Influence of Women Entrepreneurial Leadership on Employee Performance with Innovative Work Behavior as an Intervening - Arifa, Difa Putri; Rumijati, Aniek; Robbie, Iqbal (Universitas Airlangga, 2025)
Employee performance is an important element that plays a role in determining the success of an organization, because the achievement of goals and the company's competitiveness are highly dependent on the quality and productivity of employees. Along with increasing competition in the global market, companies must understand and identify factors that can optimize employee performance, both in terms of motivation, leadership, and work environment. The importance of women's leadership in the business world is getting more attention, especially in the context of diversity and inclusion. This study aims to analyze the effect of women's entrepreneurial leadership on employee performance through innovative work behavior. This study uses a quantitative approach. The data collection method in this research is observation and a questionnaire. The analytical tool used is SEM PLS 4. The population subjects in this study were employees at SME of Sari Murni, Tulungagung, totaling 40 people. In the sampling technique in this study. The result of this study found that women's entrepreneurial leadership has a significant effect on employee performance. Women's entrepreneurial leadership has a significant effect on innovative work behavior. Innovative work behavior has no significant effect on employee performance. Innovative work behavior is not able to mediate the relationship between women's entrepreneurial leadership on employee performance